2011
DOI: 10.1158/1078-0432.ccr-10-1276
|View full text |Cite
|
Sign up to set email alerts
|

Riluzole Enhances Ionizing Radiation–Induced Cytotoxicity in Human Melanoma Cells that Ectopically Express Metabotropic Glutamate Receptor 1 In Vitro and In Vivo

Abstract: Purpose: Brain metastases are a common preterminal event in patients with metastatic melanoma and require radiation therapy. Our group has previously shown that human GRM1 (hGRM1) expressing melanoma cells release excess extracellular glutamate and are growth inhibited by riluzole, an inhibitor of glutamate release. Riluzole-treated cells accumulate in G 2 /M phase of the cell cycle at 24 hours, and then undergo apoptotic cell death. We evaluated whether riluzole enhanced radiosensitivity in melanoma cells.Exp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
43
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 29 publications
7
43
0
2
Order By: Relevance
“…In accordance with an important role for Grm1 in melanomagenesis [3], we had previously demonstrated that inhibition of glutamate release by riluzole, an FDA-approved drug for the treatment of amyotrophic lateral sclerosis (ALS), suppressed human melanoma cell growth in vitro and xenograft tumor progression in vivo [21, 26, 27]. In a Phase 0 clinical trial using single agent riluzole for 14 days in patients with resectable stage III/IV melanoma, 34 % of them showed significant decrease in p-AKT and/or p-ERK expression in post-treatment tumor samples, in association with significant decrease in melanoma metabolic activity by FDG-PET [28].…”
Section: Resultsmentioning
confidence: 92%
“…In accordance with an important role for Grm1 in melanomagenesis [3], we had previously demonstrated that inhibition of glutamate release by riluzole, an FDA-approved drug for the treatment of amyotrophic lateral sclerosis (ALS), suppressed human melanoma cell growth in vitro and xenograft tumor progression in vivo [21, 26, 27]. In a Phase 0 clinical trial using single agent riluzole for 14 days in patients with resectable stage III/IV melanoma, 34 % of them showed significant decrease in p-AKT and/or p-ERK expression in post-treatment tumor samples, in association with significant decrease in melanoma metabolic activity by FDG-PET [28].…”
Section: Resultsmentioning
confidence: 92%
“…In particular, mGluRs have been shown empirically to be the predominant mediators of glutamatergic signaling in many cancers (Khan et al, 2011; Koochekpour, 2013; Martino et al, 2013; Speyer et al, 2014; Teh and Chen, 2012; Zhang et al, 2015). The mechanisms by which mGluRs modulate peripheral cell transformation and tumor growth are postulated to be either ectopic expression of wild type mGluRs, increased proliferative signals arising from receptor overexpression, mutations, or expression of polymorphic variants (Ali et al, 2014; Brocke et al, 2010; Mehta et al, 2013; Namkoong et al, 2007; Wall et al, 2014; Zhang et al, 2015).…”
Section: Mglurs In Cancermentioning
confidence: 99%
“…Although radiosensitizers have previously not been shown to provide survival benefit in human melanoma, Khan and colleagues (Khan et al, 2011) hypothesized that riluzole may be different, as cells in the G2/M phase rendered by riluzole treatment would be extremely sensitive to radiation (Ballo and Ang, 2004; Ballo et al, 2006; Eichler et al, 2007; Habermalz and Fischer, 1976). In vitro studies showed that mGluR1-positive human melanoma cells were significantly less likely to survive following ionizing radiation treatment at the 2 and 4Gy dose levels when pre-treated with riluzole at 25μM concentration, while there was negligible effect in mGluR1- negative human melanoma cells even at 100μM of riluzole treatment.…”
Section: Mglur1 As a Therapeutic Target In Treating Melanomamentioning
confidence: 99%
See 1 more Smart Citation
“…Riluzole is a noncompetitive inhibitor of metabotropic glutamate receptor-1 (GRM1) that has been shown to slow the progression of amyotropic lateral sclerosis. 176,177 GRM1 is expressed in 60% of human melanomas, and ectopic expression of GRM1 in melanocytes in a murine model resulted in development of melanocytic lesions that were indistinguishable from melanoma. 178 Activation of GRM1 results in activation of the MAPK pathway in a BRAF and N-RAS independent manner.…”
Section: Clinically Evaluated Agents Targeting Akt Signalingmentioning
confidence: 99%